(untitled) (Baghdad Science Journal, 2013)
Abstract: The aim of the present work is to measure radon concentration in wood. Solid state nuclear track detectors of type CR – 39 was used as measurement device. Eight different samples of imported and local wood were collected from markets. Samples were grinded, dried in order to measure radon concentrations in it. Cylindrical diffusion tube was used as detection technique. Results show that the higher concentration was in Iraqi sample 1 which recorded (14.02 ± 0.9) Bq / m3, while the less was in Emirates Sample which recorded (5.35 ± 1.2) Bq / m3. From the present work, all wood samples were with lowest concentrations of radon gas than other building materials.